PENGUKURAN PERUBAHAN SUHU PADA PHANTOM JARINGAN TUBUH AKIBAT SHORT WAVE DIATHERMYPADA KONDISI HYPOTHERMIA DAN HYPERTHERMIA - Lamidi .; Moch Prastawa (Poltekkes Kemenkes Surabaya, 2016)
Using the same method to study MEASUREMENT OF TEMPERATURE CHANGESIN PHANTOM BODY TISSUE DUE TO SHORT wave diathermy, Lamidi, 2014, by changing thetemperature setting conditioners phantom into three conditions, namely normal, hypothermia, andHypertermia.Tujuan this study was to determine the pattern of warming given by SWD on thethree conditions of the arm.phantomPhantom arm Hypothermia conditioned at a temperature of 32oC, Normal 37oC andhyperthermia 39oC shows the distribution of temperature that is different after being exposed toshortwave dhiathermy. With the highest temperature on the condition of hyperthermia.Hypothermia on the conditions on the distribution of temperature for 15 minutes average valueobtained 32,61oC. Normal temperature values obtained at 36.7oC. On the condition of hyperthermiathere is an average rise in temperature into the temperature distribution on 39,14oC. Laying depthaffect the resulting temperature sensors at each sensor. Average with four temperature sensorsplaced at different depths 32,65oC values obtained on condition of Hypothermia. At normaltemperature average value of 37,1oC.Pada laying conditioned sensor Hypertermia averagetemperature obtained 39,1oC.